Komunikasi Interpersonal antara Bidan dan Ibu Hamil di Puskesmas Biak Kota Provinsi Papua - Irna Deviana Dewi Safdyant; Hepi Hastuti; Jelita Purnamasari; Ismail Ibrahim (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Interpersonal communication has an important role in creating good relationships between individuals. Interpersonal communication is used in the medical situation so that someone can talk openly about the conditions and problems they are experiencing. The aim of this research is to find out how interpersonal communication is between midwives and pregnant women at the Biak City Health Center, Papua Province. The method used is descriptive qualitative. The researcher conducted observations at the Biak City Community Health Center when pregnant women underwent pregnancy checks which was handled by midwives and interviews were conducted with 5 informants to complete the data. The 5 informants in this study consisted of 3 pregnant women and 2 midwives. The results of this study show that effective interpersonal communication between midwives and pregnant women is showed by the attitudes such as: (1) openness which makes the information conveyed well absorbed, (2) empathy which makes the midwife better understand the condition of pregnant women, (3) ) positiveness in which midwives always greet pregnant women in a friendly manner to create a comfortable atmosphere, (4) support is given to pregnant women by maintaining the emotional stability of pregnant women, and (5) equality where midwives always prioritize the rights of pregnant women as their patients